1978
DOI: 10.2307/3053285
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Police on Crime

Abstract: The effect of police practices on the rate df robbery in 35 large American cities is estimated by a set of simultaneous equations. The measures of police resources (patrol units on the street) and police activity on the street (moving citations issued) are more precise than. anything thus far available in studies of this kind and permit the use l" identification restrictions that allow stronger inferences about the causal effect of arrests on crime rates than has heretofore been possible. Police resources and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(115 citation statements)
references
References 16 publications
6
107
0
2
Order By: Relevance
“…Police claim that high levels of such police proactivity have crime-control benefits, and research tends to bear those claims out (Boydstun 1975; Sampson and Cohen 1988;Whitaker et al 1985; Wilson and Boland 1978; also see Cohen and Ludwig 2003;McGarrell et al 2001;Sherman and Rogan 1995;Rosenfeld et al 2014). But critics point to frequent violations of constitutional limits on police authority, and racially disparate impacts, as reasons to more closely regulate police-initiated contacts.…”
Section: Survey Methodologies the Police Services Surveymentioning
confidence: 99%
“…Police claim that high levels of such police proactivity have crime-control benefits, and research tends to bear those claims out (Boydstun 1975; Sampson and Cohen 1988;Whitaker et al 1985; Wilson and Boland 1978; also see Cohen and Ludwig 2003;McGarrell et al 2001;Sherman and Rogan 1995;Rosenfeld et al 2014). But critics point to frequent violations of constitutional limits on police authority, and racially disparate impacts, as reasons to more closely regulate police-initiated contacts.…”
Section: Survey Methodologies the Police Services Surveymentioning
confidence: 99%
“…15 Papers in this literature employ a wide variety of econometric approaches. Early empirical papers such as Ehrlich (1973) and Wilson and Boland (1978) focused on the cross-sectional association between police and crime. discussion in the literature was whether police reduce crime at all.…”
Section: Police Manpowermentioning
confidence: 99%
“…He suggested that reform cities were more likely to adopt a legalistic style of policing because the political culture of the city suggested that the 'best' administrator should be hired for the job and then be left free of political interference. These professional managers were then likely to appoint police chiefs in favor of vigorous "professional" law enforcement (Wilson & Boland, 1978). The watchman style was more likely to be found in partisan cities with elected mayors and city councils, who were more susceptible to group interests.…”
Section: Local Politics and Criminal Justice Outcomesmentioning
confidence: 99%